Serotype spectrum of S. pneumoniae in children after the introduction of pneumococcal vaccine in Uzbekistan - E. A. Shamansurova; M. P. Kostinov (LLC "Diagnostics and Vaccines", 2024)
Assessment of the effect of vaccination against Streptococcus pneumoniae on the serotype spectrum of pneumococcus.Materials and methods. Bacteriological study of nasopharyngeal mucus of 247 healthy children attending kindergarten, as well as serotyping of the obtained samples. The specific immune response to various serotypes of S. pneumoniae was determined by ELISA.Results. A bacteriological study of nasopharyngeal mucus from 247 healthy children attending kindergarten showed that S. pneumoniae was isolated from 35.6% (20) of practically healthy children. When serotyping the isolated samples, the most common pneumococcal serotypes were 15A/F, 6 A/B, 9 A /V and 9 F, then in frequency 5 and 7 A/F, 23F serotypes. A study of specific antibodies to pneumococcus in vaccinated children showed a high level of immune response. Thus, it was found that vaccination with commercial pneumococcal vaccines protects the majority of vaccinated children. To assess the effectiveness of vaccination, it is necessary to study the circulation of serotypes in children after vaccination.